Comparison of the electrospray ionization (ESI) responses of penicillins with ESI responses of their methanolysis products. Issue 4 (August 2019) - Podniesińska, Lidia; Frański, Rafał; Frańska, Magdalena
The electrospray ionization (ESI) responses, defined as the area of chromatographic peak of ion [M +H] + obtained upon HPLC/ESI-MS analysis, of three β-lactam antibiotics, namely penicillin G, ampicillin and carbenicillin have been compared with the ESI responses of their methanolysis products. It has been found that methanolyzed penicillin G has much higher ESI response than the penicillin G. Methanolyzed ampicillin also has higher ESI response than ampicillin; however, the effect is less pronounced than for penicillin. Methanolyzed carbenicillin does not have pronouncedly higher ESI response than carbenicillin.